2017
DOI: 10.1016/j.pec.2017.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Development and field testing of a decision support tool to facilitate shared decision making in contraceptive counseling

Abstract: Objective We developed and formatively evaluated a tablet-based decision support tool for use by women prior to a contraceptive counseling visit to help them engage in shared decision making regarding method selection. Methods Drawing upon formative work around women’s preferences for contraceptive counseling and conceptual understanding of health care decision making, we iteratively developed a storyboard and then digital prototypes, based on best practices for decision support tool development. Pilot testi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 45 publications
(34 reference statements)
1
63
0
Order By: Relevance
“…‘My Birth Control’ (MBC) (https://clinic.mybirthcontrol.org/),21 ‘Birth Control Navigator’ (BCN) (https://mydoctor.kaiserpermanente.org/ncal/birthcontrol/)22 and ‘My Contraception Tool’ (MCT) (https://www.brook.org.uk/our-services/category/my-contraception-tool)23 are all web-based decision aids. The first two were developed in the USA and the third in the UK.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…‘My Birth Control’ (MBC) (https://clinic.mybirthcontrol.org/),21 ‘Birth Control Navigator’ (BCN) (https://mydoctor.kaiserpermanente.org/ncal/birthcontrol/)22 and ‘My Contraception Tool’ (MCT) (https://www.brook.org.uk/our-services/category/my-contraception-tool)23 are all web-based decision aids. The first two were developed in the USA and the third in the UK.…”
Section: Resultsmentioning
confidence: 99%
“…Some pilot testing of MBC was undertaken as part of the development process. Using the tablet-based MBC decision aid prior to consultation, and then sharing the printout with the provider, was associated with greater client satisfaction, and most of the 41 women using it (96%) reported that it helped them choose a method 21…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…61 Additional shared decisionmaking tools are being developed that will increase future educational options for women and obstetric care providers, including integration of chronic health conditions into the recommendations. 62,63 We recommend that contraceptive counseling programs be patient-centered and provided in a shared decision-making framework to avoid coercion (BEST PRACTICE).…”
Section: Patient Educationmentioning
confidence: 99%
“…95 The tool includes newly developed content to help women consider their reproductive goals and to learn about fertility and preconception health, as well as an adapted version of a previously tested patient-centered contraceptive decision support module that helps women align their values and preferences with their contraceptive choices. 96 MyPath is designed to be used prior to a primary care visit, and provides women an opportunity to identify topics and questions they would like to discuss with their provider as they progress through the tool. These topics are then summarized at completion in a print-out that can be brought to the Veteran's visit to help them to communicate effectively with their providers and to promote patient-centered counseling.…”
Section: Web-based Patient-facing Reproductive Planning Toolmentioning
confidence: 99%